Efecto de la velocidad de ensayo en las curvas de tensión-deformación de aluminio compuesto y fibra de vidrio (2024)
In this degree project, the effect of speed on tensile tests performed on two composite materials, such as Alucobond and fiberglass, is analyzed by means of laboratory tests on test tubes based on the most appropriate standard, in which the speed at which the test is performed will be varied to determine the relationship between speed and its mechanical properties and in the same way identify the material and perform its characterization, given that the variation in speed resembles the failure conditions in materials since the chance of the conditions that a material faces in certain situations can cause it to face more than one deformation speed and in this way know the behavior in these scenarios and not only with the parameters that are guided when performing the tests under standards and be able to prevent or avoid early failures or unexpected fatigue in the materials previously mentioned.